Scleroderma: a case report - Sankhe, Prachi; Patel, Spandan; Dave, Dhaval; Chandrakar, Santwana; Shetty, Varun; Nabar, S. T.; Bhate, Archana (International Journal of Research in Medical Sciences, 2017)
Scleroderma is systemic multi organ autoimmune disorder characterized by hardening of skin. Also known as systemic sclerosis. Estimated annual incidences of approximately 19 cases per million persons. The limited skin disease has a 10-year survival rate of 71%, whereas those with diffuse skin disease have a 10-year survival rate of just 21%. Risk is higher in women than men and peak in individuals aged 30-50 years. It has no definitive treatment. It may be limited or diffuse depending upon manifestations of symptoms or signs affecting internal organs especially lungs, heart, or kidney. We report a case of scleroderma with pulmonary hypertension and interstitial lung disease in our hospital who presented with tightening of skin, joint pain, dysphagia, and breathlessness. On examination skin appeared dark, shiny, and tight, with loss of hair, paraesthesia and digital ulceration. Patient also has history of Raynaud’s phenomenon. On investigation, Scl-70 and ANA (antinuclear antibodies) by enzyme immunoassay came positive. HRCT thorax was suggestive of interstitial fibrosis and PFT revealed moderate restriction. On 2D echocardiography, mild pulmonary hypertension was present while barium swallow showed motility disorder involving oesophagus. On view of extensive systemic involvement like skin, respiratory system, gastrointestinal system and heart, we would like to present this rare disorder.